Examen General de Egreso de Licenciatura Agronómica: Determinantes del Puntaje - Córdova Duarte, Gabriel; Valencia Posadas, Mauricio; Barbosa Jaramillo, Elva Rosa (Acta Universitaria, 2007)
This research determined some factors which had an impact on the scores obtained on the General Bachelor’s Degree Exam (GBDE) applied to graduates from the University of Guanajuato. The statistical analysis was performed using a factorial analysis of variance, the Spearman correlation, multiple regression analysis, and Tukey’s range test. Results showed that male students who obtained a grade point average bigger than 8.2 at college and that took the general exam during October 2000, obtained the best test scores. The highest negative correlation was estimated between the grade point average obtained at college and the number of courses failed. According to the regression analysis, the most important variables were the grade point average obtained at college and the year they took the exam. The factors that had the greatest impact on GBDE scores were essentially gender, grade point average obtained at college, the high school attended, and the month and year the exam was taken.